MDGs That Nudge : The Millennium Development Goals, Popular Mobilization, and the Post-2015 Development Framework - Gauri, Varun (World Bank, Washington, D.C., 2013)
The Millennium Development Goals, which expire in 2015, were a global agreement to promote human development and reduce poverty. But they did not create a legalized institutional regime, in which precise obligations would be delegated to specific actors, nor were they, in many respects, compatible with the incentives of the countries whose heads of state endorsed them. They most resembled international human rights treaties, which are also not legally coercive, and which achieve their effects largely through their role in social and political mobilization. But unlike human rights treaties, the Millennium Development Goals' targets and goals were not psychologically, morally, and politically salient. The goals and targets for the proposed second round of Millennium Development Goals should be easier to grasp and embed within them a causal narrative about the causes and remedies of global poverty. Their formulation and implementation should also draw on national institutions and processes, which most people find more persuasive than discussions at the international level. The paper develops these ideas and presents examples for how post-2015 development goals and targets might be presented in ways that are more compelling.